Promoting Persuasion With Ideologically Tailored Science Messages: A Novel Approach to Research on Emphasis Framing. Issue 4 (August 2019) - Luong, Kate T.; Garrett, R. Kelly; Slater, Michael D.
Motivated reasoning in response to disconfirming science information presents a challenging barrier to science communication. This article presents a novel approach to emphasis framing, in which functionally equivalent information is framed using ideologically consistent values and tailored to the audiences. In contrast to traditional framing approaches, science information is held constant across frames and only interpretations of the information are varied. Results from an experiment provide initial support for this ideology-based framing approach. Persuasive effects are stronger for an ideologically congruent frame than for an incongruent frame, and no boomerang effects were observed. We discuss implications and directions for future research.